(untitled) (Heritage, 2024)
Miloš Kordić (1944) belongs to writers who have been on the stage for more than half a century and his oeuvre includes poetry, poetry for children, essays, short stories, novels, nonfiction. Kordić’s creative attention is constantly focused on the emerging phenomena of the world and the manifestations of life, in which he discovers the sublimation of the new, the world rich in symbols and meanings. He advocates for a non-anthropocentric picture of the world, for surrealist representations of fluid realities and mystical connections between things and phenomena, in which the "realm of meaning" is revealed. His poetry is characterized by a metaphysical obsession with sensations of the miraculous in the sphere of the everyday; creative absorption of the outside world and interweaving of different spheres of physical and metaphysical reality. Kordić very often moved in the spaces of memory and primordial memory or pre-memory (both mythological and historical), spaces of dream - oneiristic and, especially, spaces of metaphysics, observing and sensory perceiving the invisible world in visible, manifest forms; and, perhaps more importantly, in contemporary events. The collection Grlo u rebrima (2023) offers a world of shades and appearances, vague knowledge and undefined spaces, filled with paradoxes, contrasts, illogical images and astonishment. His landscapes are metaphysical, whether they are made up of images of everyday life (images and smells of childhood from Banija, Sunja and Sisak, on the one hand, and images of chaotic daily life in Belgrade caught by war and bombing, on the other hand), or, on the other hand, images of epic and the mythical past, with which, through symbols and dreams, it is constantly called. The motifs and images of his poems carry elements of surrealist poetics, mystery, mysticism, ambiguity and suggestiveness, which is why they can easily be linked to the metaphysical painting of George De Chirico and his famous painting "The Secret and Melancholy of the Street".